Some Properties of Fuzzy Soft Proximity Spaces - İzzettin Demir; Oya Bedre Özbakır (The Scientific World Journal)
We study the fuzzy soft proximity spaces in Katsaras’s sense. First, we show how a fuzzy soft topology is derived from a fuzzy soft proximity. Also, we define the notion of fuzzy soft δ-neighborhood in the fuzzy soft proximity space which offers an alternative approach to the study of fuzzy soft proximity spaces. Later, we obtain the initial fuzzy soft proximity determined by a family of fuzzy soft proximities. Finally, we investigate relationship between fuzzy soft proximities and proximities.